2016
DOI: 10.1007/s12040-016-0725-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of groundwater vulnerability in El-Bahariya Oasis, Western Desert, Egypt, using modelling and GIS techniques: A case study

Abstract: The Nubian Sandstone Aquifer (NSSA) is the main groundwater resource of the El-Bahariya Oasis, which is located in the middle of the Western Desert of Egypt. This aquifer is composed mainly of continental clastic sediments of sandstone with shale and clay intercalations of saturated thickness ranging between 100 and 1500 m. Vulnerability assessment to delineate areas that are more susceptible to contamination from anthropogenic sources has become an important element for sustainable resources management and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 15 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…Hamdam et al [16] reported transmissivity values between 236 m 2 /d and 3045 m 2 /d as a result of 12 pumping tests conducted in the Nubian sandstone aquifer in the El-Bahariya oasis, about 300 km northwest of the Kharga oasis. Masoud and Osta [17] analyzed 26 pumping tests in the Nubian sandstone aquifer of the El-Bahariya oasis and reported transmissivity values between 191 m 2 /d and 970 m 2 /d; the discrepancy with the previous study was not explained.…”
Section: Introductionmentioning
confidence: 69%
“…Hamdam et al [16] reported transmissivity values between 236 m 2 /d and 3045 m 2 /d as a result of 12 pumping tests conducted in the Nubian sandstone aquifer in the El-Bahariya oasis, about 300 km northwest of the Kharga oasis. Masoud and Osta [17] analyzed 26 pumping tests in the Nubian sandstone aquifer of the El-Bahariya oasis and reported transmissivity values between 191 m 2 /d and 970 m 2 /d; the discrepancy with the previous study was not explained.…”
Section: Introductionmentioning
confidence: 69%
“…Other geological formations include El-Heiz formation, El-Hefhuf formation, and Quaternary deposits (El-Sisi et al, 2002;Khalifa et al, 2006). The Bahariya Oasis, initially developed during the lower Eocene due to tectonic movements which is now occupied by a major depression floor dotted by several isolated residual hills and is surrounded by escarpments from the northern and eastern parts (Hamdan 2012;Masoud and El-Osta, 2016) (Fig. 2b).…”
Section: Study Site Descriptionmentioning
confidence: 99%
“…The main water resource for irrigating the reclaimed areas ( Fig. 2d) in this Oasis is groundwater stored within the Nubian Sandstone Aquifer (NSSA) (Masoud and El-Osta, 2016). Groundwater is susceptible to anthropogenic activity resulting from urbanisation, increase in populations, land reclamation, increase of agricultural activities and lack of proper sewage and irrigation drainage systems (El-Sisi et al, 2002).…”
Section: Study Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the view of these weaknesses, there is a strong requirement for reassessment of groundwater resources using pioneer technology such as Geographic Information System (GIS), Global Positioning System (GPS), and Remote Sensing (RS) (Srivastava et al 2013;Singh et al 2014). The growth of these tools has also prepared another time and cost impressive means of groundwater potential analysis (Nampak et al 2014;Masoud and El Osta 2016). So, according to Davoodi Moghaddam et al (2015), groundwater potential analysis can be very useful and helpful for managers to prepare best management scenarios of water resources in any region.…”
Section: Introductionmentioning
confidence: 99%